Species and Density of Gastropods in the Mangrove Ecosystem of the Apar Village, North Pariaman District, West Sumatera Province - sovia, Vina; Fajri, Nur El; Sumiarsih, Eni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractMangrove forest in the Apar Village has been degraded due to anthroponegic activities. The activities counducted in that area damage the mangrove and thus negatively affects gastropods living in that area. A research aims to identify gastropods species and density was conducted in july 2019. There was 2 stations, with 3 plots/station and 5 subplots/plot. In each subplot, the gastropod were collected by hand. There were 11 gastropod species present, namely Telescopium telescopium, Cerithideaquadrata, Faunus ater, Neritinaturrita, Neritinasemiconica, Nerita lineate, Neritodryasdubia, Ellobiumaurisjudae, Cassidulaaurifelis, Thiarascabra and Littorinascabra. Density of gastropod ranges from 0,066-2,667 organisms/. The Water quality were as follows : temperature 26-32˚C; soil temperature 29-33˚C; pH 7; soil pH 5-6 and salinity  4-22 ‰ Keywords: Cerithideaquadrata, water quality, mangrove forest, anthroponegic activities, salinity